Ultrasound appearance of intravenous leiomyomatosis: A case report. Issue 35 (August 2019) - Ge, Zhitong; Wang, Yahong; Qi, Zhenhong; Zhang, Qing; Jin, Jin; Li, Jianchu
Abstract: Rationale: Intravenous leiomyomatosis (IVL) is a rare benign smooth muscle tumor that can develop from the pelvic or uterine veins and spread into the central veins and heart. Here, we report a case of recurrent IVL in a 48-year-old woman. To the best of our knowledge, this is the first case report of IVL that describes the characteristic ultrasound features of the tumor, including the rainbow sign. Patient concerns: A 48-year-old woman developed a solid-cystic lesion in the inferior vena cava (IVC) 3 years after undergoing a right heart tumor resection and 5 years after undergoing hysterectomy. Diagnoses: Physical examination was unremarkable. However, ultrasonography showed a solid-cystic lesion in the IVC, and a diagnosis of IVL was made. Interventions: The patient underwent complete surgical removal of the tumor by a multidisciplinary team. The tumor was resected successfully. Outcomes: Pathological examination confirmed that the IVC tumor thrombus was consistent with IVL. During follow-up, there were no signs of local or distant recurrence. Lessons: The preoperative diagnosis of IVL is difficult, and the tumor is usually misdiagnosed as a thrombus or right atrial myxoma. A thorough understanding of the characteristic imaging features of IVL is essential for an accurate preoperative diagnosis. The lesion in our patient showed multiple tracts, a honeycomb appearance, and vividly colorful blood flow that resembled a rainbow, which we termed the rainbow sign.